On referee bias, crowd size, and home advantage in the English soccer Premiership - Johnston, R. (Journal of Sports Sciences, 2008)
In a recent paper in this journal, Boyko and colleagues (2007) identified differences in attendance and referee bias as factors influencing home advantage at soccer matches in the English Premiership. A replication of their study using more recent data found no evidence to sustain either of their claims.